Probabilidade de falha de coroas com infraestrutura em zircônia com diferentes geometrias - Ramos, Gabriela Freitas [UNESP] (2014)
This study evaluated the failure probability of fully or partially porcelain / glaze veneered crowns, determining their failure probability with Weibull analysis. Sixty molars were selected and prepared for first molar full crown and divided into three groups (n = 20): Traditional -crowns with zirconia infrastructure covered with feldspathic porcelain; Modified - crown partially covered with veenering porcelain and Monolithic - Full countour zirconia crown. All specimens were treated with glaze layer. Specimens were submitted to mechanical cycling (100 N, 3 Hz) using a piston (Ø = 6 mm) until the specimens failure or up to 2 x 106 cycles. Every 500,000 cycles the specimens were inspected for the presence of flaws in stereomicroscope (10×). The predominant type of failure was cracking and chipping of the feldsphatic porcelain, followed by delamination and debonding . Weibull parameters (beta and eta), with two-sided confidence interval of 95 %, were respectively: Traditional - 1,25 and 0,09 E + 07 cycles ; Modified- 0,58 and 1,16 E + 07 cycles; Monolithic - 1,05 and 1,64 E + 07cycles. Traditional crowns showed greater susceptibility to fatigue, the Modified group presented higher propensity to early failures, and Monolithic showed no susceptibility to fatigue. Modified and Monolithic presented then highest number of crowns presenting no failures after the fatigue test. The three crown designs presented quite different behaviors under fatigue. The two modified groups presented less probability to failure after 2 x 106 cyles